2023
DOI: 10.3389/fphys.2022.1064168
|View full text |Cite
|
Sign up to set email alerts
|

Human in vitro assay for irreversible electroporation cardiac ablation

Abstract: Introduction: Pulsed electric field (PEF) cardiac ablation has been recently proposed as a technique to treat drug resistant atrial fibrillation by inducing cell death through irreversible electroporation (IRE). Improper PEF dosing can result in thermal damage or reversible electroporation. The lack of comprehensive and systematic studies to select PEF parameters for safe and effective IRE cardiac treatments hinders device development and regulatory decision-making. Human induced pluripotent stem cell-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 85 publications
2
20
0
Order By: Relevance
“…Significant cardiomyocyte recovery was observed following PFA, with resumption of electric activity in 40% to 67% of the initial functional lesion within 1-hour post-PFA. Consistent with previous reports, 33 , 34 , 38 protocol modifications could influence the extent of reversible electroporation, with a tight spatial correlation between the expected distribution of the electric field intensity and the eventual occurrence of irreversible electroporation. These observations have important clinical consequences, as the immediate development of localized electric silencing and functional conduction blocks does not necessarily mean long-term persistence of these lesions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Significant cardiomyocyte recovery was observed following PFA, with resumption of electric activity in 40% to 67% of the initial functional lesion within 1-hour post-PFA. Consistent with previous reports, 33 , 34 , 38 protocol modifications could influence the extent of reversible electroporation, with a tight spatial correlation between the expected distribution of the electric field intensity and the eventual occurrence of irreversible electroporation. These observations have important clinical consequences, as the immediate development of localized electric silencing and functional conduction blocks does not necessarily mean long-term persistence of these lesions.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous in vivo and in vitro reports, including recent studies utilizing hiPSC-CMs. 13,14,33,34,37,41 In regions of the culture subjected to lower field intensities, a delayed recovery of electric activity could be detected. These findings further emphasize that initial electric silencing following PFA does not necessarily translate into durable lesions, and that recovery of electric activity may occur over the course of hours/days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data evaluating the molecular effects of PFA on cell cultures have revealed a differential response and toxicity threshold from both murine and human cardiomyocytes, neurons, and cardiac adipocytes based on electric field strengths [ 43 , 44 , 45 , 46 , 47 ]. Human esophageal smooth muscle cells have also been assessed and exhibited a greater resistance to FPA [ 48 ].…”
Section: Pulsed-field Ablation For Arrhythmogenic Substrate Suppressionmentioning
confidence: 99%
“…9 Toward that end, we have shown that hiPSC-CM models are sufficient to evaluate various cardiac electrophysiology device signals in vitro, including novel cardiac ablation modalities and acute CCM parameters. 7,[10][11][12][13][14] Human 3D cardiac microphysiological systems, including hiPSC-CM engineered cardiac tissues (ECTs), cardiac microtissues or cardiac microbundles, are established models for the acute evaluation of cardiac electrophysiology medical device signals and cardiac drugs. 12,15 However, such models may not be appropriate for long-term chronic in vitro studies.…”
Section: Introductionmentioning
confidence: 99%